Effectiveness of learning time for physical education sports and health at Senior High School 10 Malang - Prawira Adityamawardhana Putra; Mashuri Eko Winarno (Indonesian Journal of Research in Physical Education, Sport, and Health, 2023)
This study aims to determine the effectiveness of learning hours for physical education, sports, and health at Senior High School 10 Malang by using quantitative and qualitative descriptive methods. Data collection was carried out by researchers through observation and documentation techniques. The results showed that PJOK learning time was not effective at Senior High School 10 Malang, with an average time of 68 minutes as a percentage of the total time of 76%. However, the average pre-activity duration was 7 minutes (8%), the average duration of the core activities was 55 minutes (61%), and the average duration of the final activity was 6 minutes (7%). The conclusion of this study is that the hours of learning sports, physical education, and health at Senior High School 10 Malang are not very effective. The study hours for PJOK subjects at school do not meet the guidelines. According to these guidelines, each learning activity carried out by the teacher consists of 10% preparatory/preparatory activities, 80% core activities, and 10% final/closing activities.